2017
DOI: 10.24869/psyd.2017.136
|View full text |Cite
|
Sign up to set email alerts
|

Use of Electroconvulsive Therapy in Central-Eastern European Countries: An Overview

Abstract: SUMMARY Though a number of reports on the use of electroconvulsive therapy (ECT) has been published from the Central-Eastern

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 13 publications
1
34
0
10
Order By: Relevance
“…However, heterogeneity in ECT delivery, both nationally and internationally, is a concern. A comprehensive contemporary review of worldwide ECT practice and variability demonstrated substantial heterogeneity [2] with high variability in the United States [3][4][5], Canada [6,7], Australia [8], the Netherlands [9], Belgium [10], Central and Eastern Europe [11], Greece [12], Spain [13], the Baltic States [14], Saudi Arabia [15], South Africa [16], Nigeria [17], Russia [18], Thailand [19], Japan, [20], India [21] and other Asian countries [22,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, heterogeneity in ECT delivery, both nationally and internationally, is a concern. A comprehensive contemporary review of worldwide ECT practice and variability demonstrated substantial heterogeneity [2] with high variability in the United States [3][4][5], Canada [6,7], Australia [8], the Netherlands [9], Belgium [10], Central and Eastern Europe [11], Greece [12], Spain [13], the Baltic States [14], Saudi Arabia [15], South Africa [16], Nigeria [17], Russia [18], Thailand [19], Japan, [20], India [21] and other Asian countries [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…sine wave devices), and inconsistently uses electroencephalogram (EEG) monitoring, anesthesia and paralytic medications. This is most likely due to limited financial or medical resources and contrasts with more contemporary ECT practice in North America, Western Europe, Australia, and New Zealand where brief or ultrabrief pulse stimulation, active EEG monitoring and routine anesthesia are more regularly used [2,11,22].…”
Section: Introductionmentioning
confidence: 99%
“…A general overview of use of electroconvulsive therapy in Central-Eastern European countries was recently given by Gazdag et al (2017). ECT practice in this region shows a heterogeneous picture as of utilization rate, prevailing indications and technical parameters.…”
Section: Discussionmentioning
confidence: 99%
“…[178][179][180] Globally, use of ECT is heterogeneous, [181][182][183][184][185][186][187] and geographic limitations, lack of training, lack of anesthesiologists, cost, stigma, health-care inequity, and national laws have been described as obstacles to access. 183,[188][189][190][191][192] Outdated treatment protocols and heavy use for conditions less responsive to ECT (ie, schizophrenia) are common across Asia, based on a study of 334 institutions in 29 Asian countries. 193 In Scandinavia, ECT is widely available and tends to follow updated treatment guidelines, but unequal geographic distribution can limit access.…”
Section: Under-recognition Of Catatoniamentioning
confidence: 99%